The 1α-hydroxy-A-rings of norditerpenoid alkaloids are twisted-boat conformers. Issue 32 (18th May 2020) - Zeng, Ziyu; Qasem, Ashraf M. A.; Kociok-Köhn, Gabriele; Rowan, Michael G.; Blagbrough, Ian S.
Abstract : The skeletal conformations of naturally occurring norditerpenoid alkaloids fix their substituent functional groups in space, thereby directing their bioactivities. Abstract : The skeletal conformations of naturally occurring norditerpenoid alkaloids fix their substituent functional groups in space, thereby directing their bioactivities. Solution conformations of the A-rings of 4 selected norditerpenoid alkaloid free bases: mesaconitine, karacoline (karakoline), condelphine, and neoline (bullatine B), were analysed by NMR spectroscopy and single-crystal X-ray crystallography. They adopt twisted-chair, twisted-boat, twisted-boat, twisted-boat conformations, respectively. That the A-ring is stabilised in a boat conformer by an intramolecular H-bond from 1α-OH to the N -ethyl tertiary amine is also confirmed in the condelphine single crystal data. The conformations are a result of through-space repulsion between 12-He′ and atoms attached to C1 (in the equatorial positions). This causes the A-rings with 1α-OR always to be twisted whether in a chair or a boat conformation. The impact of these studies is in providing a detailed understanding of the shape of the A-ring of these important biologically active natural product alkaloids.